Discovery of super soft-drug modulators of sphingosine-1-phosphate receptor 1. Issue 19 (15th October 2018) - Bell, Mark; Foley, David; Naylor, Claire; Robinson, Colin; Riley, Jennifer; Epemolu, Ola; Scullion, Paul; Shishikura, Yoko; Katz, Elad; McLean, W.H. Irwin; Wyatt, Paul; Read, Kevin D.; et al.
Graphical abstract: Highlights: Identification of soft drug S1PR agonists. Development of a process for the evaluation of topical esterase soft drugs. Study skin and plasma esterase SAR. Abstract: The oral S1PR1 agonist ponesimod demonstrated substantial efficacy in a phase II clinical trial of psoriasis. Unfortunately, systemic side effects were observed, which included lymphopenia and transient bradycardia. We sought to develop a topical soft-drug S1PR1 agonist with an improved therapeutic index. By modifying ponesimod, we discovered an ester series of S1PR agonists. To increase metabolic instability in plasma we synthesised esters described as specific substrates for paraoxonase and butyrylcholinesterases, esterases present in human plasma.